“People Gathered by Sorghum”: Cultural Practices and sorghum Diversity in Northern Ethiopia - Wendmu, Tsedal Asres; Gebrelibanos, Tesfakiros Semere; Kovi, Mallikarjuna Rao; Ring, Kristoffer Hofaker; de Boer, Hugo J.; Abera, Fetien Abay; Westengen, Ola Tveitereid (Human ecology : an interdisciplinary journal, 2023)
Sorghum is an important crop in the livelihoods of Kunama and Tigrayan farmers in Northern Ethiopia and we present here a study of what factors have shaped the genetic diversity of the varieties cultivated in neighboring communities of the two ethnolinguistic groups. Using a combination of methods from crop science and cultural anthropology, we investigate patterns of historical and contemporary relationships between crop genetic diversity and cultural and social factors. The spatial genetic structure reveals patterns of ethnolinguistic differentiation and admixture that reflect deep affinities between cultures and crops, but the seed systems of the two communities are also open to exchange and gene-flow. Our findings highlight the importance of understanding cultural factors for genetic resource conservation, as well as for plant breeding and seed system development efforts.